2019
DOI: 10.3390/e21050465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Advective-Diffusive Transport of Multiple Chemoattractants on Motility of Engineered Chemosensory Particles in Fluidic Environments

Abstract: Motility behavior of an engineered chemosensory particle (ECP) in fluidic environments is driven by its responses to chemical stimuli. One of the challenges to understanding such behaviors lies in tracking changes in chemical signal gradients of chemoattractants and ECP-fluid dynamics as the fluid is continuously disturbed by ECP motion. To address this challenge, we introduce a new multiscale numerical model to simulate chemotactic swimming of an ECP in confined fluidic environments by accounting for motility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Their simulations revealed that any irregularity on wall surfaces could cause temporary or permanent clogging of the flow field if hydrodynamic forces on the particle cannot overcome unevenly distributed repulsive barrier on the channel wall. Başağaoğlu et al used the LJ 6-12 model to simulate chemotatic motility [220] or flow [221,222] of circular particles in a Newtonian fluid, settling or flow of a mixture of non-circular particles in a Newtonian fluid, and flow of a mixture of non-circular particles in a non-Newtonian fluid [145,146]. Using the LJ 6-12 potentials, Başağaoğlu et al [146] demonstrated that steady vortices do not necessarily always control particle entrapments nor do larger particles get selectively entrapped in steady vortices in a microfluidic chamber.…”
Section: Lennard-jones Potentialsmentioning
confidence: 99%
“…Their simulations revealed that any irregularity on wall surfaces could cause temporary or permanent clogging of the flow field if hydrodynamic forces on the particle cannot overcome unevenly distributed repulsive barrier on the channel wall. Başağaoğlu et al used the LJ 6-12 model to simulate chemotatic motility [220] or flow [221,222] of circular particles in a Newtonian fluid, settling or flow of a mixture of non-circular particles in a Newtonian fluid, and flow of a mixture of non-circular particles in a non-Newtonian fluid [145,146]. Using the LJ 6-12 potentials, Başağaoğlu et al [146] demonstrated that steady vortices do not necessarily always control particle entrapments nor do larger particles get selectively entrapped in steady vortices in a microfluidic chamber.…”
Section: Lennard-jones Potentialsmentioning
confidence: 99%
“…In subsequent work [31], we couple RapidCell with the lattice-Boltzmann method [32] to simulate how engineered micro-particles utilize E. coli's biased random walk to detect the location of high chemical concentration contained in a confined zone with a narrow inlet or concentric multiringed inline obstacles, mimicking tumor vasculature geometry. In [33], instead of imposing static concentrations as in [29,31], we implement dynamic multiple concentrations of different chemicals to show how the chemotactic behavior changes over time as the cells disturb and mix the chemicals.…”
Section: Introductionmentioning
confidence: 99%